SOCIO-ECONOMIC INEQUALITY IN UKRAINE IN THE MEASUREMENT OF GLOBAL INDEXES - Berveno, S.; Berveno, O.; Zlobin, V. (Komunalʹne hospodarstvo mist, 2024)
The current period of socio-economic development in Ukraine and the world is characterized by the exacerbation of the problems of inequality in its various forms in the global, regional and national perspectives. Inequality between people, its manifestations, causes, trends are the subject of theoretical and applied research by scientists from various fields of knowledge - philosophy, sociology, economics, law, etc. Currently, various aspects of social, economic, gender inequality, etc. are being studied. Various aspects of socio-economic inequality are analyzed in the works of Ukrainian scientists, including: V. Adamyk, O. Berveno, N. Koval, V. Opalko, etc. But its essence and characteristics have not yet received a systematic disclosure, which actualizes research in this area of social relations. The purpose of the article is to reveal the factors of socio-economic inequality in Ukraine, the directions of its reduction based on the analysis of the dynamics of global index indicators that characterize certain aspects of social development in the modern period. The article substantiates the relevance and expediency of using global indices as an effective tool for analyzing the current state, forms and trends of socio-economic inequality. According to the indicators of the Global Social Progress Index, the Human Development Index, the Global Gender Gap Index and other global indices, the main factors of deepening socio-economic inequality in Ukraine in the current period are revealed and measures to reduce it are justified. Socio-economic inequality is an integrative unity of economic and social inequalities, which necessitates the combination of its economic and social dimensions in the analysis process, which will allow substantiating its state, manifestations and trends in a certain period of time. Global indices, in particular the Global Social Progress Index and the Human Development Index, whose indicators cover a complex of economic and social characteristics of social development, should be recognized as effective research tools. Currently, socio-economic inequality in Ukraine is deepening, as evidenced by the downward dynamics of the indicated global indices. Measures are proposed to minimize socio-economic inequality in Ukraine.